The effect of hopelessness and perceived group compatibility on treatment outcome for patients with personality dysfunction - Aafjes-van Doorn, Katie; Ehrenthal, Johannes C. (The journal of nervous and mental disease, 2020)
Improvement in life satisfaction is hard to achieve for any patient with personality psychopathology, and possibly even moreso for those who feel hopeless at the start of treatment. The present research investigated the potential influence of hopelessness in the treatment of patients with personality dysfunction, using data from patients who completed an intensive group therapy program designed to reduce symptom distress and support optimal psychosocial functioning (N = 80). In the present study, we sought to examine whether hopelessness would moderate (i.e., strengthen or weaken) relations between compatibility ratings and life satisfaction outcome. Hopelessness had a significant moderating effect on the relationship between compatibility and outcome, suggesting that, for patients who entered treatment feeling more hopeless, higher appraisals of fit within the group facilitated better gains in life satisfaction. If replicated, the findings underlie the importance of focusing on increasing hope and perceived group affiliation in the treatment of personality dysfunction.
Gesehen am 16.12.2020